Long-Term Stroke Risk in Patients Undergoing Left Atrial Appendage Ablation With and Without Complete Isolation - Dhorepatil, Aneesh; Lang, Angela L.; Lang, Min; Butt, Muhammad; Arbune, Amit; Hoffman, David; Almahmeed, Soufian; Ziv, Ohad (Frontiers in Cardiovascular Medicine, 2021)
Background: Catheter ablation (CA) for atrial fibrillation (AF), may require ablation beyond the pulmonary veins. Prior data suggest that additional LA ablation, particularly left atrial appendage (LAA) ablation, may alter atrial function leading to increased risk of ischemic stroke or transient ischemic attack (IS/TIA). We sought to study the long-term risk of IS/TIA in patients receiving ablation at the LAA compared to those receiving PVI alone and those receiving PVI with additional non-LAA locations. Methods: 350 patients who underwent CA for AF from 2008 to 2018 were included in the study. Locations of ablation in LA evaluated were the posterior wall, anterior wall, inferior wall, inter-atrial septum, lateral wall and the left atrial appendage (LAA). Patients undergoing LAA ablation were further divided as complete isolation (LAAi) and without complete isolation (LAAa). Results: Mean follow up of 4.8 years. In entire cohort, risk of IS/TIA was 1.62/100 patient‑years (pys). The risk was highest in patients with LAAi (3.81/100 pys), followed by ablation LAAa (3.74/100 pys). Amongst all LA locations, only LAAi (HR 3.32 p=0.03) and LAAa (HR 3.18, p=0.02) were statistically significant predictors of IS/TIA after adjusting for OAC (Oral anticoagulant) use and baseline CHA2DS2VASc score. Conclusions: During long term follow-up, only ablation at the left atrial appendage with and without complete isolation was independently associated with an increased risk of IS/TIA in patients undergoing CA for AF. Potential strategies to reduce stroke risk, such as LAA closure, should be considered in these patients.